Pemanfaatan Media Tiga Dimensi Pop Up Book dalam Meningkatkan Hasil Belajar IPA Materi Ekosistem pada Siswa Kelas V SDN 03 Clering Donorojo Jepara - Cahyono, Gatot Pujo; Widiyono, Aan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research is based on the atmosphere of the learning process that is alive and effective, less active students and low learning motivation and learning outcomes of students in grade V SDN 03 Clering. This study aims to determine how effective the application of Pop-Up Book media is in improving science learning outcomes of ecosystem material in grade V elementary school students